Factors affecting the youth watch "manoto" satellite network - abdolrahman alizadeh; zarrin zardar (مطالعات رسانه‌های نوین, 2018)
The Effective Factors on Satellite Televisions' Spectacle and Appealing to Youth Audiences; with Special Emphasis on MANOTO Satellite Channel In recent years, the portion of satellite televisions in youth audiences’ media consumption, have dramatically increased. This caused big challenges and concerns for policy makers, media staff and other stakeholders and led them to seek for an answer to this crucial question: why satellite TVs are this appealing to youth audiences and what factors could be effective on their attention to the Persian satellite TVs programs – especially MANOTO channel, the most popular satellite TV among Iranian youth audiences. To answer this question,tehranian youth audiences (18-35 years old) selected by non-random purposive sampling. qualitative interview method carried out by semi-structured in-depth interviews and focus groups and analyzed by thematic analysis as a technic. According to findings, youth audiences identified fifteen factors, appealing them to satellite TVs. The factors were categorized into four universal codes which included: representation of taboos, intimacy and youth, empowering the audiences and infotainment. It seems that MANOTO and other satellite channels gives alternative point of view to the Iranian youth audiences which is silenced in national Television channels.